Prevalence of Adenomyosis in Hysterectomy Specimens Performed at a Tertiary Hospital of Kathmandu, Nepal - Pande, Kricha; Koirala, S; Giri, A (Nepal Medical College Journal, 2020)
Adenomyosis is a common condition, detected in 15-30% of hysterectomy specimens. It is characterized by the presence of endometrial glands and stroma within the myometrium. The data regarding incidence or incidental finding of adenomyosis in hysterectomy specimen is lacking despite this condition being common and bearing serious implications in symptomatology as well as in infertility. Adenomyosis can be incidental finding in hysterectomy done for other gynecologic pathology as well. Hence, this present study has established the prevalence of adenomyosis as well as it’s association with other uterine pathology in routine hysterectomy specimens. This was a cross sectional study conducted at Nepal Medical College and Teaching Hospital (NMCTH), Kathmandu for a duration of one year (March 2019 to February 2020). Total of 154 hysterectomies were included in the study, out of which 37 cases showed adenomyosis. The prevalence of adenomyosis was 24%. The age group for adenomyosis ranged from 36 years to 52 years with the mean age of 44 ± 4.4 years. The most common pathology other than adenomyosis was leiomyoma (19 cases) followed by two cases of endometriotic cyst, two cases of endometrial polyp, one case of high grade squamous intraepithelial lesion (HSIL), one case of hyperplasia of endometrium with atypia, and one case of serous cyst adenoma of ovary. Thus this study showed that the prevalence of adenomyosis was 24% and was seen higher in the age group of 35-50 years. The most frequent co-pathology in these adenomyosis cases was leiomyoma.